SOLID LIPID NANOPARTICLE DEVELOPMENT FORMULATION TRANSDERMAL DOSAGE FORM OF FUROSEMIDE AND IN VITRO TESTING - Forestryana, Dyera
Background: Furosemide is a potent diuretic agent with a half life 45-60 minutes and oral bioavailability about of 50%. Transdermal dosage form is used to improve bioavalability of furosemide, but stratum corneum acts as barrierfor penetration furosemide pass through the skin. To overcome this problem, solid lipid nanoparticles (SLN) is formulated to increase penetration furosemide (FRS) pass through the stratum corneum. Objective: Aims of the study is to develop a formulation of SLN as a carrier of furosemide and physicochemical evaluation including to in vitro diffusion test. Methods: SLN FRS formulation was prepared by combination of high-speed homogenization and ultrasonication method. SLN formulation consists of 10% apifil, 8% plantacare and 0.5% furosemide. Characterization study was accomplished to particle size measurement, polydispersity index, potential zeta measurement, entrapment efficiency (EP), melting point, morphology, physicochemical stability and in vitro diffusion test. Results: Particle size of obtained SLN was in the range of 50-100 nm with polydispersity index (PI) of less than 0.5 and potential zeta value of -4.64 mV. Entrapment efficiency furosemide in SLN was 75.82 ± 6.71%. Morphology by Transmission Electron Microscopy (TEM) revealed spherical shapeof SLN. DSC thermogram showed a solidification of lipid after formulation process. The Physical evaluation of SLN furosemide showed that SLN was relative stable at room temperature during storage within 90 days, and the particle size slightly increasing observed at 40 0 C. Furosemide content in SLN during 28 days at room temperature and 40 0 C was relative stable. In vitro diffusion test showed that FRS has been penetrated with amount of 134.33 µg/cm 2 and flux of 32.42 ?g/cm 2 /hour from SLN cream dosage form. In addition, 296.93 µg/cm 2 and flux of 107.10 µg/cm 2 / hour of furosemid was penetrated from SLN gel dosage form. According to one way ANOVA statistic design showed that there is significant improvement of SLN formulation in compare to conventional formulation (p <0.05).